Long-term results of treatment of right-sided colon cancer with mesocolic excision and D3-lymph node dissection - S. K. Efetov; I. A. Tulina; A. Yu. Kravchenko; D. N. Fedorov; S. V. Efetov; P. V. Tsarkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
Aim of investigation. To estimate efficacy of D3-lymph node dissection with mesocolic excision in comparison to standard surgical technique of right hemicolectomy for right colon cancer in long-term terms.Methods. Comparative analysis of the long-term results of treatment of right colon cancer at I–III stages with D2- and D3-lymph node dissections was carried out. Traditional right hemicolectomy with D2-lymph node dissection was applied in 132 patients (control group). Patients after right hemicolectomy with D3-lymph node dissection, mesocolic excision with «notouch» principles have been included to the main group (n=64). Groups were comparable by demographic and clinical features, and also by stage of local neoplastic spread.Results. Significant differences in general cumulative 5-years survival rate (69 and 86% respectively, р=0,043) and 5-years cancer-specific survival rate (91 and 71% respectively, р=0,014) have been revealed between control and main groups. Among patients with involved lymph nodes (III stage) overall 5-years survival rate after standard surgery (58%) was worse, than after right hemicolectomy with D3-lymph node dissection (83%, p=0,042). In patients with D2-lymph node dissection the involvement of regional lymph nodes was significant prognostic factor deteriorating overall 5-years survival rate (p=0,039) while at D3-lymph node dissection this factor had no effect on the prognosis (p=0,535).Conclusion. At right colon cancer of I–III stages D3-lymph node dissection is the major factor significantly improving overall 5-years survival rate. Extended lymph node dissection is the factor levelling negative prognostic effect of metastatic lymph node involvement which can be accomplished by prevention of local lymphogenic relapse of tumor.